PENGARUH MOTIVASI KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT FLUID SCIENCES BATAM - Victor Manek Mali, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
The research is made under the title “The Influence of Work Motivation and Compensation on Employee Performance at PT Fluid Sciences Batam .” The purpose of this research is to find out how much the influence of work motivation and compensation on employee performance at PT Fluid Sciences Batam. Data collection techniques used in this study in the form of research by distributing questionnaires and literature studies. Research method using quantitative research technique. The number of sample in this research is 66 respondents.The result showed that the regression equation formed was Y =-3,438 + 0,496X1 + 0,767X2. The results of this study indicate that alone, work motivation has a positive and significant effect on employee performance and compensation has a positive and significant effect on employee performance. While together, work motivation and compensation have positive and significant effect on employee performance at PT Fluid Sciences Batam . This decision is based on a significance level of F value of 0.000 smaller than a = 0.05.